Critical size defect regeneration using PEG-mediated BMP-2 gene delivery and the use of cell occlusive barrier membranes - the osteopromotive principle revisited - Wehrhan, Falk; Amann, Kerstin Ute; Molenberg, Aart; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2013)
Objective: The objective of this study was to investigate if osseous regeneration can be accelerated by involvement of periosteal tissue. Bone defect regeneration could be accelerated by the involvement of periosteal tissue if osteogenic cell signalling is maintained within the defect. It was questioned if local cell-mediated BMP-2 gene delivery makes a cell occlusive membrane dispensable during bone critical size defect regeneration. Methods: PEG matrix (degradation time 10 days) and PEG membrane (degradation time 120 days) were used in the pig calvarial model. Cylindrical (1 × 1 cm) critical size defects (CSD) (9 per animal; 20 animals) were filled with: (i) particulated autologous bone, covered with PEG membrane (group 1); (ii) HA/TCP, covered with PEG membrane (group 2); (iii) HA/TCP, mixed with PEG matrix (group 3); and (iv) HA/TCP mixed with BMP-2-transfected osteoblasts and PEG matrix (group 4). BMP-2/4 gene transfer: liposomal in vitro transfection of BMP-2/V5-tag fusion-protein. Quantitative histomorphometry (toluidine blue staining) after 2, 4 and 12 weeks assessed bone formation. Semiquantitative immunohistochemistry estimated the expression of BMP-2, V5-tag, Runx-2 and Sox9. Results: PEG matrix embedded BMP-2 expressing cells presented higher bone formation (P < 0.05) than HA/TCP + PEG matrix defect filling or PEG membrane covering (HA/TCP filling) after 12 weeks. Highest expression of BMP-2, Runx-2 and lowest expression of fibrous tissue marker Sox9 was seen in the BMP-2 group. Conclusion: PEG matrix embedded BMP-2 expressing cells are capable to maintain osteogenic signalling and to accelerate osseous defect regeneration in absence of a cell occlusive membrane. © 2012 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: BMP; Bone regeneration; Gene transfer; Hydrogel; Immunohistochemistry; Osteogenesis